Review on selective production of acetophenone from oxidation of ethylbenzene over heterogeneous catalysts in a decade - Nandanwar, Sachin U.; Rathod, Simmy; Bansal, Videsha; Bokade, Vijay V. (Catalysis Letters, 2021)
The consumption of acetophenone (AP) is increasing worldwide because of its applications in products such as alcohol, aldehydes, resins, esters, fragrances, and pharmaceuticals. AP is manufactured via several methods like decomposition of cumene hydroperoxide, Hock process, and Friedel-Crafts acylation reaction using homogeneous catalysts with solvent and oxidant. However, it causes several environmental problems that deteriorate the production of AP with these methods. Oxidation of ethylbenzene (EB) is one of the promising methods to synthesize AP in liquid and vapor phases reaction using heterogeneous catalysts, which plays a vital role for selective production of AP. In this review, numerous heterogeneous catalysts are discussed including transition metal nanoparticles, transition metal complexes, and metal free catalysts (carbon nanotubes) used in last 10 years for oxidation of EB. Additionally, catalyst activity along with reaction parameters and its effect, mechanisms, and kinetics study are summarized in this article. The future scope of this reaction is also highlighted. Moreover, this work identifies best catalysts for bulk production of AP with high yield to satisfy global requirement.
Keywords: acetophenone; ethylbenzene; Heterogeneous catalysts; Oxidation reaction; reaction mechanisms